PSYCHO-PHILOSOPHICAL TEACHINGS OF JIDDU KRISHNAMURTI: A PARADIGM FOR ENHANCING HUMAN LIFE - Mohan, Vinitha (International Journal of Psychosocial Rehabilitation, 2019)
Jiddu Krishnamurti’s philosophy offers profound insights into the nature of truth and existence, emphasizing the importance of direct observation and liberation from conditioned thinking. The article explores Krishnamurti’s rejection of fixed paths to truth, advocating for a holistic understanding of life that transcends intellectual knowledge and emotional entanglements. It delves into his critiques of psychological conditioning, the limitations of ideologies, and the necessity for inner revolution. Krishnamurti’s perspective on the mind, consciousness, fear, and identification is elucidated, highlighting his call for freedom from all constructs of the mind. Ultimately, Krishnamurti’s philosophy emphasizes living in the present moment with attention and awareness, fostering genuine transformation and the realization of truth in everyday life.